Characterization of semi-coke generated by coal-based direct reduction process of siderite - Zhu, De-qing; Luo, Yan-hong; Pan, Jian; Zhou, Xian-lin (Journal of Central South University, 2015)
Solid wastes derived from metallurgical industries pose a significant threat to environment. The utilization and disposal of these solid wastes are the major concern in the world. Semi-coke generated in coal-based direct reduction process of iron ore is a by-product and its suitable utilization is not available so far. In order to handle it properly, the characteristics of this by-product were comprehensively investigated. A series of analysis methods were used to demonstrate its mineral compositions, petrography and physico-chemical properties. The results reveal that the semi-coke has poor washability. The fixed carbon content of semi-coke reaches 76.11% and the gross calorific value is 28.10 MJ/kg, both of which are similar to those of traditional sinter coke breeze. Also, semi-coke ash possesses lower content of SiO 2 , Al 2 O 3 , S and higher content of CaO and MgO, which could improve the strength of sinter ore when partially substituting for coke breeze in sintering. Semi-coke features well-development porous structure and higher reaction activity, which predicts that the sintering speed could be elevated to some extent when employing it as a partial replacement of coke breeze, so the studies further suggest that the potential adverse effect of the high reactivity on sintering process could be weakened by adequately coarsening the semi-coke’s particle size.